Should We Learn from Srikandi Panghegar to Break The Discrimination and Stigma Against Transwomen? - Uliviana Restu Handaningtias; Ika Arinia Indriyany; Nadia Malika Farhanah (Universitas Multimedia Nusantara, 2023)
Heteonormativity is a view that makes transwomen a subject of discrimination and stigma. The discrimination and stigma received by transwomen in Cianjur Regency are inseparable from the construction of the Cianjur community, which is predominantly by Islamic values as the basis for society to normalize these actions. Cianjur is a city in West Java that has a strong history of Islamic movements in West Java. The life of the Cianjur people is influenced by Sundanese and Islamic cultures, which mingle in the joints of the community's social, cultural, and political life. Srikandi Panghegar exists as a community that fights against heteronormativity in Cianjur Regency. This study uses the theory of social movements from the perspective of LGBT, as proposed by Mary Bernstein (1997) with a qualitative research method using a case study approach, the results of this study explain the spread of identity as a method used in collective action as the goal of social movements in terms of gaining acceptance of stigmatized identities to change institutions. However, Srikandi Panghegar Cianjur has not yet reached the stage of changing institutions because movement mobilization is still focused on the community itself and movements only on a small scale at the district level. The spread of identity can then be examined in two forms: identity for critique (identity for criticism) and identity for education (identity for education).